The Role of Social Support in Substance Addiction Recovery: A Systematic Review - Rokiyah Rokiyah; Natalia Zuanda; Alrefi Alrefi; Akbari Akbari (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
Recovery from substance addiction is a complex process that requires continuous physical and psychological support. Social support plays a crucial role in assisting individuals through the process of substance addiction recovery. This article presents a systematic review of the role of social support in substance addiction recovery by analyzing relevant studies from various academic sources. The findings indicate that social support, whether from family, friends, or community, significantly enhances individuals' motivation, resilience, and success in maintaining long-term recovery. Various forms of support, such as emotional, instrumental, and informational support, help individuals cope with the challenges of recovery. Additionally, participation in support groups and positive interpersonal relationships have been shown to accelerate the recovery process and prevent relapse. Therefore, social support is a key element not only in facilitating recovery but also in improving the quality of life for individuals dealing with substance addiction.